Wages, Experience, and Training of Women over the Life Cycle - Blundell, Richard; Costa-Dias, Monica; Goll, David; Meghir, Costas (Journal of Labor Economics, 2021)
We investigate the role of training in reducing the gender wage gap using the British Household Panel Survey. On the basis of a life-cycle model and using tax and welfare benefit reforms as a source of exogenous variation, we evaluate the role of formal training and experience in defining the evolution of wages and employment careers, conditional on education. Training is potentially important in compensating for the effects of children, especially for women who left education after completing high school, but does not fundamentally change the wage gap resulting from labor market interruptions following child birth.